1996
DOI: 10.1111/j.1439-0442.1996.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Studies on Experimental Oleander Poisoning in Cattle

Abstract: W t h 9jigum.r (Received forpubhationJanua3, 17, 1996) s-aiy Oleander poisoning has been reported in man and animals. The present experiments address the gross and microscopic changes due to oleander poisoning in cattle. Minimum lethal doses (50 mg&) of oleander leaves were orally administered to three calves in a single dose and each of the other three animals received the same lethal dose in three equal parts with 24-h intervals. The lesions in the three animals which received 50 mg/kg in a single dose re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
2
19
1
4
Order By: Relevance
“…Oleander is an evergreen plant, widespread all over the world, belonging to the Apocynaceae family, whose most prevalent species are Nerium oleander (common oleander) from the Mediterranean basin and Asia [1] and Thevetia peruviana (yellow oleander) from tropical America [2]. Its toxicity has been known since ancient times: in India, before Christ, the shrub was called Kajamaraka, "the herb that makes the horse die" [3].…”
Section: Introductionmentioning
confidence: 99%
“…Oleander is an evergreen plant, widespread all over the world, belonging to the Apocynaceae family, whose most prevalent species are Nerium oleander (common oleander) from the Mediterranean basin and Asia [1] and Thevetia peruviana (yellow oleander) from tropical America [2]. Its toxicity has been known since ancient times: in India, before Christ, the shrub was called Kajamaraka, "the herb that makes the horse die" [3].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these results indicated that rats are more susceptible than mice, as more severe pathological lesions and also severe changes in the values of troponin were noted. In experimental oleander poisoning in cattle and albino mice congestion, haemorrhage, coagulative necrosis, fibromyolysis of the cardiac muscle fibres, and cell infiltration between muscle fibres, epicardium, and endocardium was reported (19,23). Moreover, in another experimental study in broiler chickens, myocardial cell necrosis with hyperaemia and haemorrhage were observed (22).…”
Section: Discussionmentioning
confidence: 98%
“…O quadro clínico-patológico observado na intoxicação por N. oleander é causado pela ação de glicosídeos cardí-acos que atuam sobre a bomba de sódio e potássio, resultando em diminuição do K intracelular e aumento do K sérico, o que causa diminuição da condutividade elétrica no coração, arritmias e eventual parada cardíaca (RietCorrea & Méndez 2007). As lesões microscópicas cardía-cas foram semelhantes às descritas na intoxicação experimental em bovinos (Oryan et al 1996, Tokarnia et al 1996 e ovinos (Armién et al 1994). Tanto nos casos naturais, como nos experimentais, as lesões foram mais significativas no músculo papilar do coração.…”
Section: Discussionunclassified
“…Nerium oleander, popularmente conhecida como "espirradeira" (Armién et al 1994) e originária do Mediterrâneo e Ásia (Oryan et al 1996, Kellerman et al 2005, é cultivada como planta ornamental em muitas partes do Mundo (Aslani et al 2004). Todas as partes da planta contêm glicosídeos cardiotóxicos (Armién et al 1994, Osweiler 1995, oleandrina e neriina (Galey 2004).…”
Section: Introductionunclassified